2018
DOI: 10.2340/00015555-2885
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Treatment for Pityriasis Rubra Pilaris: A Case Series and Literature Review

Abstract: Treatment recommendations for pityriasis rubra pilaris (PRP) are based solely on case reports and small case series, as to-date no randomized controlled trials are available. We present here a case series of 3 patients and a literature review of 28 studies treating a total of 116 patients, with the aim of providing data regarding efficacy and safety of methotrexate in the treatment of PRP. Methotrexate was effective in our patients; the review showed an overall response rate of 65.5% with complete clearing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
3
12
0
2
Order By: Relevance
“…In accordance with previously published reviews, treatment with other immunosuppressive medications (MTX or cyclosporine) was reported to be moderately effective with PRP . However, a recent review emphasized the role of MTX in the treatment of PRP due to positive response rates in two‐thirds of 116 patients and good tolerability, and concluded that it should be considered as a first‐line treatment . Moreover, patients seemed to rate therapy with MTX and therapy with retinoids as equally helpful in a larger case series .…”
Section: Discussionsupporting
confidence: 74%
“…In accordance with previously published reviews, treatment with other immunosuppressive medications (MTX or cyclosporine) was reported to be moderately effective with PRP . However, a recent review emphasized the role of MTX in the treatment of PRP due to positive response rates in two‐thirds of 116 patients and good tolerability, and concluded that it should be considered as a first‐line treatment . Moreover, patients seemed to rate therapy with MTX and therapy with retinoids as equally helpful in a larger case series .…”
Section: Discussionsupporting
confidence: 74%
“…In Übereinstimmung mit früher publizierten Übersichtsarbeiten wurde die Behandlung mit anderen Immunsuppressiva (MTX oder Cyclosporin) bei PRP als mäßig wirksam beschrieben . Eine kürzlich publizierte Übersicht betonte jedoch wegen des positiven Ansprechens bei zwei Dritteln der 116 Patienten und der guten Verträglichkeit den Nutzen von MTX zur Behandlung der PRP und zog den Schluss, das Medikament als Erstlinien‐Behandlung in Betracht zu ziehen . Darüber hinaus schienen die Patienten aus einer umfangreicheren Fallserie die Therapie mit MTX als ebenso hilfreich einzustufen wie eine Therapie mit Retinoiden .…”
Section: Diskussionunclassified
“…Methotrexat stellt eine Alternative für Patienten dar, wenn Retinoide kontraindiziert sind, nicht ausreichend wirken oder nicht vertragen werden [5,22,45]. Eine kürzlich veröffentlichte systematische Analyse der Literatur der letzten 50 Jahre konnte ein relativ gutes Ansprechen auf Methotrexat bei überwiegend guter Verträglichkeit belegen [46]. Es werden Dosen zwischen 5 bis 25 mg wöchentlich (mit Folsäuresupplementation am Folgetag) eingesetzt [43].…”
Section: Histologieunclassified